K-Popers and ARMY BTS: An uprising subculture community in Indonesia - Yayah Cheriyah; Amanda Rochima Hadi (SIMULACRA: JURNAL SOSIOLOGI, 2022)
This article investigated the fans’ identity among ARMY BTS Indonesia, the fandom name for BTS fans. The study aimed to explore factors driving K-Pop fanaticism in Indonesia in general and how it affected their dynamics within the society. Using a quantitative method through online surveys based on the fans-identity scale approach, the research surveyed a total of 243 fans in Indonesia using a network sampling approach. Results showed that fans were considerably proud to be recognized as BTS fans. In terms of the drives of their fanaticism, three main factors played into the role namely: the enjoyment feelings surged when listening to BTS music, the emotional connection toward BTS, and the social connection. These three factors were well correlated, reflecting the same construct. The latter incorporated the fans’ fascination toward idols’ works and their need to actively participate in online platforms. Fans’ participation in online platforms not only catered for their need to socialize with fans alike and showcase their adoration toward their idols but also being able to proudly show their identity as loyal fans.